Epigenetic Regulation of Monoallelic Rearrangement (Allelic Exclusion) of Antigen Receptor Genes - Levin-Klein, Rena; Bergman, Yehudit (Frontiers in Immunology, 2014)
While most genes in the mammalian genome are transcribed from both parental chromosomes in cells where they are expressed, approximately 10% of genes are expressed monoallelically, so that any given cell will express either the paternal or maternal allele, but not both. The antigen receptor genes in B and T cells are well studied examples of a gene family which is expressed in a monoallelic manner, in a process coined "allelic exclusion". During lymphocyte development, only one allele of each antigen receptor undergoes V(D)J rearrangement at a time, and once productive rearrangement is sensed, rearrangement of the second allele is prevented. In this minireview, we discuss the epigenetic processes, including asynchronous replication, nuclear localization, chromatin condensation, histone modifications and DNA methylation, which appear to regulate the primary rearrangement of a single allele, while blocking the rearrangement of the second allele.